2014
DOI: 10.1177/1074248414546324
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine’s Efficacy as an Antiplatelet Agent Study in Healthy Volunteers

Abstract: This study suggests that HCQ has antiplatelet properties possibly through the AA pathway (downstream to thromboxane A2 production). With possible additional beneficial effects over the traditional CVD risk factors, larger studies in the future might explore HCQ's potential as an antiplatelet agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 33 publications
1
39
0
2
Order By: Relevance
“…CQ does not inhibit cyclo-oxygenase-1 (COX-1) whereas HCQ is a modest inhibitor of this enzyme in whole blood (BenChetrit et al 2005), and this is probably a factor in its effects on platelet aggregation. A study by Achuthan et al (2015) in human volunteers showed that prior treatment for 7 or 14 days with HCQ resulted in a 11 % reduction in arachidonic acid-induced platelet aggregation, but not when adenosine disphosphate or collagen was used as agonists, thus confirming the site of action of HCQ on COX-1. However, of particular interest are the observations by these authors that a combination of HCQ and an anti-platelet dose of aspirin had markedly increased inhibitory effects on platelet aggregation but this did not relate to decrease in serum levels of 11-dehydroxy-thromboxane B 2 (the stable metabolite of thromboxane A 2 ) compared with that from aspirin or HCQ.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 83%
See 1 more Smart Citation
“…CQ does not inhibit cyclo-oxygenase-1 (COX-1) whereas HCQ is a modest inhibitor of this enzyme in whole blood (BenChetrit et al 2005), and this is probably a factor in its effects on platelet aggregation. A study by Achuthan et al (2015) in human volunteers showed that prior treatment for 7 or 14 days with HCQ resulted in a 11 % reduction in arachidonic acid-induced platelet aggregation, but not when adenosine disphosphate or collagen was used as agonists, thus confirming the site of action of HCQ on COX-1. However, of particular interest are the observations by these authors that a combination of HCQ and an anti-platelet dose of aspirin had markedly increased inhibitory effects on platelet aggregation but this did not relate to decrease in serum levels of 11-dehydroxy-thromboxane B 2 (the stable metabolite of thromboxane A 2 ) compared with that from aspirin or HCQ.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 83%
“…Several lines of investigation have indicated that HCQ may have anti-thrombotic activity (Petri et al 2012) partly as a result of its actions on arachidonic acid metabolism and inhibition of platelet activation and adhesion to the sub-endothelium (Gallus, 1979;Achuthan et al 2015). CQ does not inhibit cyclo-oxygenase-1 (COX-1) whereas HCQ is a modest inhibitor of this enzyme in whole blood (BenChetrit et al 2005), and this is probably a factor in its effects on platelet aggregation.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…A retrospective study in RA patients concluded that hydroxychloroquine 400 mg/ day offers significant, independent protection against cardiovascular morbidity 21 . Hydroxychloroquine is also reported to possess anti-platelet and antithrombotic properties [22][23][24] . The ultimate objective of treatment is to reduce cardiovascular risk.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, it is not known, if the efficacy of HCQ in different rheumatic and autoimmune diseases is mediated by different mechanisms. The previously described actions of HCQ include reduction of cytokine production,12–14 inhibition of immune effector cells,3 inhibition of platelet function,15 protection of the cell surface from external disturbances,16 competitive binding to nucleic acid ligands of toll-like receptors (TLRs),17 interference with lysosomal function3 5 and reduction of leakage of lysosomal enzymes 3. While some of these quite heterogeneous effects associated with HCQ might be related to each other, no unifying mechanism of action of HCQ has been found.…”
Section: Introductionmentioning
confidence: 99%